The Baptist example of social responsibility: an appraisal of the literacy programme of the Nigerian Baptist (2011)
This paper is an appraisal of the social responsibility purpose served by the Adult literacy Programme of the Nigerian Baptist Convention. The research objectives was to find out the strategies, the successes and challenges faced on the Programme, The researcher sought to know how this has improved the literacy level of the participants and the extent to which the church members have benefitted from the project. The paper examines how the Programme runs, the perception of the beneficiaries and that of the Organizers. Data was collected through in depth interview from a purposive sample drawn from among the Programme director, the teachers and the students. The researcher also gathered data by observing the actual classroom Situation. The centres visited were in Ibadan. Findings show that there were more females than males involved in the Programme both as teachers and students. Yoruba language played a pivotal role as the language of instruction. The instructors who are mostly volunteers earn very little and in most cases, no stipend. Some of the major challenges faced are lack of resources, teacher and Student mobility and low motivation